Upaya Dinas Pariwisata dalam Meningkatkan Resiliensi Pengrajin Reyog di Kabupaten Ponorogo - Nurfaidah, Galuh Diah Salsa; Nasution, Robby Darwis; Hilman, Yusuf Adam; Ridho, Irvan Nur (JURNAL NASIONAL PARIWISATA, 2024)
The aim of this research is to determine the Tourism Department's efforts to increase the resilience of reog craftsmen in Ponorogo Regency. This research is qualitative research. Data collection techniques in research are observation, interviews, and documentation, with data analysis using data collection, data reduction, data presentation, and drawing conclusions. The results of the research first show that the efforts made by the government of the Ponorogo Tourism Office to help craftsmen are by promoting their products both locally and internationally. Second, the government helps craftsmen to obtain business permits and collaborates with PKK members to support each other's businesses. Third, promote through social media to increase the economic income of craftsmen. Fourth, to strengthen increased resilience, the Ponorogo Regency Tourism Office carries out networking activities (collaborating with other people), namely establishing collaboration with other regions through participation in arts and crafts exhibitions and involving the younger generation. Researchers put forward several recommendations which can later be used as a reference, including holding exhibitions of works involving the younger generation. This is one of the efforts to make Reyog Ponorogo art more sustainable.